The role of History Education in mitigating insecurity and COVID-19 challenges in Nigeria (Czech Journal of Multidisciplinary Innovations, 2021)
History being the queen or mother of all courses especially in art and social sciences is always ready to offer a helping hand in solving difficult riddles and paradoxes bedeviling humanity such as insecurity, Covid 19 and all forms of pandemics notwithstanding! This study has as much as possible diagnosed the roles History education can play in mitigating insecurity and COVID-19 challenges in Nigeria by adopting survey research design where questionnaires were used in sampling opinions. Consequently, threat to food security, lost of lives, hunger and displacement of people are some of the discovered effects of insecurity. Meanwhile, unemployment, lack of good education, poverty etc were identified as some of the causes. However, strict adherence to government’s directives on constant hand washing, use of face mask, social distancing, provision of jobs, security of people’s lives and properties etc were recommended as possible solutions to the challenges of Covid 19 and insecurity.